Information acceptance and ICT resistance: promoting the role of information in rural community development - Mansor, Yushiana; Kamba, M.A (University of Nebraska--Lincoln Libraries, 2010)

(untitled)
Rural community development is a major issue for developing countries. Much attention has been given Information and Communication Technology (ICT) projects to connect rural communities with the global network. However, ICT resistance is a deterring factor in addressing the digital divide in developing countries. It is postulated that reversing the resistance to to ICT can be strategizedthrough "information acceptance." ICT can be accepted by rural communities by creating demand for information. The paper calls for the refocusing on the role of information in rural community development and ICT as a tool for change agent. Initiatives for rural community development must emphasize the importance of information in rural communities.